Environmental and Institutional Support: A Study of English Language Education in Pesantren Settings - Sholihah, Nanda; Ritonga, Apri Wardana; Desrani, Ayu (JELITA, 2025)
This research investigates how the pesantren environment shapes students' motivation and attitudes toward learning English and suggests strategies to improve English education in these institutions. The study employed a qualitative approach, involving eight English language teachers from pesantren schools in Cirebon and nearby regions, selected via a distributed teacher data form.The results highlight that students' motivation and attitudes are significantly influenced by institutional support, well-structured programs, and teacher-student collaboration, rather than whether the pesantren is categorized as modern or semi-modern. Pesantrens that foster immersive English environments and implement clear programs show higher levels of student motivation. Conversely, a lack of structured support contributes to disengagement. This study concludes that robust institutional strategies and collaborative efforts are pivotal for advancing English education in pesantren, offering insights into improving religious-based learning contexts.